Chemical Composition and In vitro Anthelmintic Activity of Extracts of Tagetes patula Against a Multidrug-Resistant Isolate of Haemonchus contortus - Politi, Flávio Augusto Sanches [UNESP]; Souza Júnior, Amauri Alves [UNESP]; Fantatto, Rafaela Regina [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Barioni Júnior, Waldomiro; Rabelo, Márcio Dias; Bizzo, Humberto Ribeiro; Chagas, Ana Carolina de Souza; Furlan, Maysa [UNESP] (Wiley, 2018)
Sheep breeding has suffered economic losses due to parasitism by gastrointestinal nematodes, particularly Haemonchus contortus. The use of natural products, specifically Tagetes patula, has been suggested as an alternative method of combatting this issue. Chemical analyses of the extracts of this species described in the literature report the presence of important classes of secondary metabolites such as thiophenes, flavonoids, alkaloids, and benzofurans, some of which were identified and isolated in this study. The aim of this work was to test the effect of the essential oil (EO) and the ethanolic extract of the aerial parts (TpEt OH) of T. patula on eggs and larvae of H. contortus, through an egg hatch test (EHT) and a larval development test (LDT). In the EHT, the EO showed 100% inhibition at 0.75 mg mL−1 (LC50 = 0.0780 mg mL−1), and the TpEt OH showed 100% inhibition at 100 mg mL−1 (LC50 = 12.8 mg mL−1). In the LDT, the EO showed 100% inhibition at 0.375 mg mL−1 (LC50 = 0.0400 mg mL−1), and the TpEt OH showed 100% inhibition at 1.56 mg mL−1 (LC50 = 0.340 mg mL−1). Compared to available literature data, the results presented here suggest that the crude extracts of T. patula have substantial potential for controlling this nematode by interrupting its life cycle and/or preventing it from reaching the infective stage.
Keywords: Haemonchus contortus; natural products; Tagetes patula; terpenoids; thiophenes